Structural, Morphological, Optical, and Antibacterial Activities of Zinc Oxide Nanopowders: A Comparative Study of Green and Soft Chemical Synthesis - K. Catherine Siriya Pushpa; P. Sakthivel; K. Saravanakumar; N. Anuradha; R. K. Sankaranarayanan; Mosae Selvakumar Paulraj (Advances in Materials Science and Engineering)
Zinc oxide, a well-known inorganic metal oxide in nanoparticle form, has outstanding antibacterial properties. In this work, the authors focus on determining ZnO nanoparticles’ structural, optical, and antibacterial activity. A simple soft chemical route synthesizes C-ZnO nanoparticles chemically, while the green synthesis method is used to prepare G-ZnO nanoparticles. Ocimum tenuiflorum leaf extract was used to prepare G-ZnO nanopowders. These samples are investigated and compared in terms of their structural, morphological, optical, and antibacterial properties. According to XRD investigations, the synthesized ZnO nanopowders possess a hexagonal structure. The particle size of G-ZnO is smaller than that of C-ZnO nanoparticles. The XPS result revealed the binding and interactions between molecules. The FTIR study confirmed the presence of molecules and their vibrations. UV-vis-DRS spectroscopy was used to investigate optical properties such as reflectance and band gap. The grain size of the G-ZnO nanopowders was decreased, and oxygen vacancy was produced. The antibacterial efficiency of plant extracts against two different bacterial strains, S. aureus (Gram-positive) and E.coli (Gram-negative), has been studied and reported.